Fostering gender dimensions in henna (Lawsonia inermis L.) production under arid and semi-arid conditions - Simgh, Dheeraj; Chaudhary, M.K.; Tetarwal, Chandan Kumar; Kuri, B.R. (Indian Council of Agricultural Research, 2023)
In the experiences of arid/semi-arid zone Rajasthan women farmers with limited resources, it is imperative to create alternate livelihood options with strict adherence to sustainable technologies. In this regard, henna cultivation has become highly commercialized in the Pali district, but still there is a wide gap between current production and productivity. Women’s participation in the henna (Lawsonia inermis L.)-based farming system is crucial to the sustenance of rural economy in such areas. They need to be involved in the cropping sector to considerably increase productivity. Realizing the importance and involvement of women in henna production, a study on gender dimensions in henna production was undertaken in the Pali district in Rajasthan. The degree of participation of women in henna production was determined in operations for manual participation and supervision. A knowledge test was prepared to assess the training needs pertaining to selected operations in henna growing. It is evident from the study that participation of women in different operations of henna production was very high. With women predominant at all levels—production, preharvest, post-harvest processing, packaging and even marketing—it is imperative to adopt gender-specific interventions. An inclusive, transformative agricultural policy should aim at gender-specific interventions to raise productivity of small farm holdings, integrate women as active agents in rural transformation, and engage women in extension services with gender expertise. Thus, rural women are increasing their quantum in the integrated management and use of diverse natural resources with multiple roles as cultivators, entrepreneurs and laborers.